1987
DOI: 10.1002/macp.1987.021880819
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of membranes for the dehydration of water‐acetic acid mixtures by pervaporation, 1. Polymer material selection

Abstract: Poly(viny1 alcohol) (PVA) was studied for use as a basic material for membrane preparation with the aim of dehydrating water-acetic acid mixtures. Membranes of different nature were made by blending a PVA sample of 96% hydroxyl content with a polyacid or a polybase counterpolymer in water, followed by complete evaporation. The PVA-polybase blends gave membranes of low selectivity, unsuitable for dehydration. The membrane M , , made of a 1 : 1 (by wt.) blend of PVA with a special grade of polyhydroxycarboxylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 10 publications
2
31
0
Order By: Relevance
“…This means that there would be still unreacted carboxylic acid water in the permeate increases. 3 Also, Nguyen et al 3 reported that the polyacid component fain the resulting membrane. However, it can be seen that the swelling ratio increases even if the vored the transport of water over that of acetic acid by preferential interactions.…”
Section: Swelling Behavior Of Crosslinked Pva Membranesmentioning
confidence: 98%
See 1 more Smart Citation
“…This means that there would be still unreacted carboxylic acid water in the permeate increases. 3 Also, Nguyen et al 3 reported that the polyacid component fain the resulting membrane. However, it can be seen that the swelling ratio increases even if the vored the transport of water over that of acetic acid by preferential interactions.…”
Section: Swelling Behavior Of Crosslinked Pva Membranesmentioning
confidence: 98%
“…They achieved the high separation In recent years there has been increased interest in the use of the pervaporation membrane separafactors, but the permeation rates obtained were very low. Nguyen et al 3 reported the membrane tion process for separation of organic liquid mixtures, since the pervaporation technique is considmaterial selection for the dehydration of wateracetic acid mixtures using poly(vinyl alcohol) ered to be an energy-saving process. Compared to the ethanol-water system on which many perva-(PVA) as the base polymer.…”
Section: Introductionmentioning
confidence: 99%
“…This fact suggests that the two polymers form a complex due to intermolecular hydrogen bonding between hydroxyl group of PYA and carboxyl group ofPMAA. 12 ,13 When aqueous solutions of PYA/PAA were mixed, two-phase separation occurred,14,15 or clear homogeneous aqueous solution 16 was obtained according to sample preparation conditions.…”
mentioning
confidence: 99%
“…These phenomena might be attributed to the fact that the hydrophilicity of the blend membrane increase with increasing ester groups of vinyl acetate in EVA copolymer. The permeation rate increases as the hydrophilicity increases, indicating a decrease in the cohesion between polymer chains of material used [ 12]. Thus, we investigated blends of EVA with TPX for the 40 tool % grade vinyl acetate content of EVA copolymer in this article.…”
Section: Effect Of Vinyl Acetate Content In Evamentioning
confidence: 98%